Keterlibatan Dan Sikap Konsumen Berpengaruh Terhadap Keputusan Pembelian Mobil Daihatsu Xenia Di Surabaya - Siti Tarwiyah; Endang Setyawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2014)
Various product MPV, makes has many choices in take the purchasing decision. This matter is indicated that has strong position in determines purchasing decision towards product needed, not with the exception of in the case of consumer decision in buy car xenia that be object from this watchfulness. This watchfulness aims to detect and analyze influence from consumer involvement variable and consumer attitude variable towards car purchasing decision daihatsu xenia at surabaya. Population in this watchfulness car user Daihatsu xenia at surabaya. with gather sample passes method questioner towards 100 person. Analysis that used doubled linear regression, and hypothesis testing that used test f and test t in significant standard 5%. Analysis result shows that look for information in consumer involvement level and subjective risk in consumer involvement kind very influential towards purchasing decision. access in cognate component, self confidence taste and pleasant taste in component afektif with effort supporting in component behaviour/action very influential towards purchasing decision. as to purchasing decision is influenced bigger because appropriate need.